2019
DOI: 10.3390/microorganisms8010050
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Analysis of Stable 1,4-dioxane-Degrading Microbial Consortia Consisting of Novel Dioxane-Degraders

Abstract: Biodegradation of 1,4-dioxane, a water contaminant of emerging concern, has drawn substantial attention over the last two decades. A number of dioxane-degraders have been identified, though many of them are unable to metabolically utilize 1,4-dioxane. Moreover, it is considered more preferable to use microbial consortia rather than the pure strains, especially in conventional bioreactors for industrial wastewater treatment. In the present study, a stable 1,4-dioxane-degrading microbial consortium was enriched,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Isolation and characterization of metabolic 1,4-D-degrader is of utmost importance not only to develop an efficient biological treatment system using pure culture for 1,4-D-contaminated industrial wastewater [ 13 , 16 ] but also to understand their interactions while co-existing in the 1,4-D-degrading microbial consortia known to be more effective and robust as compared to pure culture [ 15 ]. The present study isolated and identified three metabolic 1,4-D-degrading bacteria ( Pseudonocardia sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolation and characterization of metabolic 1,4-D-degrader is of utmost importance not only to develop an efficient biological treatment system using pure culture for 1,4-D-contaminated industrial wastewater [ 13 , 16 ] but also to understand their interactions while co-existing in the 1,4-D-degrading microbial consortia known to be more effective and robust as compared to pure culture [ 15 ]. The present study isolated and identified three metabolic 1,4-D-degrading bacteria ( Pseudonocardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic 1,4-D-degrading bacteria was isolated by spreading the microbial inoculum of the consortium N112 on mineral salt medium (MSM, pH 7.0) agar plates supplemented with 100 mg/L of 1,4-D. The composition of MSM used in this study is described in Tusher et al [ 15 ]. After incubating the plates at 30 °C, single colonies of distinct bacterial species were identified and inoculated into 20 mL vials containing 10 mL of sterile MSM supplemented with 100 mg/L of 1,4-D.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive characterization of microbial functional diversity is essential for a better understanding of contaminated site bioremediation [19][20][21]. However, most studies on azo dye degradation focused on isolation, identification, and characterization of culturable bacteria [22,23]. It is estimated that only 0.1-1% microorganisms are culturable using conventional methods.…”
Section: Introductionmentioning
confidence: 99%